Comparison of serum interleukin-10 level of fungal exposure among patients with pulmonary sarcoidosis and healthy people - Alavi Foumani, Seyed Ali; Geranmayeh, Siamak; Tangestani Nejad, Azita; Pour Kazemi, Aydin; Kazem Nejad Leili, Ehsan; Jafari, Alireza; Amooei Khanabbasi, Mehrzad (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Introduction: Sarcoidosis is a chronic systemic inflammatory disease with unknown etiology. Fungal exposure has been assumed as one of many possible causes of the disease. The prevalence of sarcoidosis is likely to be higher in the Northern Iran compared with other regions. Environmental studies have shown higher levels of fungal spores in the air of this area. Some studies have shown that fungal exposure in patients with sarcoidosis is associated with decreased levels of interleukin-10 (IL-10) serum levels. The aim of present study was comparison of the serum levels of IL-10 in patients with pulmonary sarcoidosis and healthy people. Objectives and Methods: In this current analytical, cross-sectional study, 40 patients with pulmonary sarcoidosis compared with 34 healthy individuals as a control group, who had been visited in a pulmonary referral clinic in Rasht (Guilan-Iran). Demographic data were collected by a questionnaire. Serum IL-10 levels were measured by ELISA kit. The data were analyzed by using the SPSS software (version 19). Results: The mean concentration of IL-10 serum levels were reported 10.96±9.48 pg/ml-1 and 3.77±1.47 pg/ml-1 among the patients with pulmonary sarcoidosis and healthy individuals, respectively. The significance difference was demonstrated between patients with pulmonary sarcoidosis and control group (p<0.0001). The IL-10 showed a significant difference between the patients older than 40 and those younger than 40. In statistical analysis, 4.75 pg.ml-1 was considered the cutoff point to separate patients and control group. Conclusion: The results showed that IL-10 was greater among patients who diagnosed as pulmonary sarcoidosis. There was a contrary opinion of the expectations for the role of fungal exposure as a possible cause of greater prevalence of sarcoidosis in Northern Iran. Age and stage of disease showed a significant relationship with the IL-10 serum level and requires further investigation. IL-10 might be a possible predictor of sarcoidosis along with other factors.